Serum MUC5AC protein levels are correlated with the development and severity of connective tissue disease-associated pulmonary interstitial lesions - Weng, Lin; Liu, Wei; Wang, Lingye; Wu, Zhichao; Liu, Dehao; Lin, Yihua; Song, Shuli; Yu, Ciyuan; Chen, Yaqiong; Chen, Juan; Ge, Shengxiang (Frontiers in Immunology, 2022)
Background: Mucin 5AC (MUC5AC) and mucin 5B (MUC5B) are the major components of airway mucins. The expression levels of MUC5AC and MUC5B are related to connective tissue disease-associated interstitial lung disease (CTD-ILD) in the promoter region of MUC5AC and MUC5B and the relevant bronchoalveolar lavage fluid. However, the serum protein levels of MUC5AC and MUC5B have not been tested in CTD-ILD patients. In this study, we tested the serum levels of MUC5AC and MUC5B proteins in CTD-ILD patients and assessed their relationship with the occurrence and development of ILD. Methods: Serum samples were obtained from 168 CTD and 80 healthy participants from the First Affiliated Hospital of Xiamen University. The serum levels of MUC5AC and MUC5B proteins were measured by enzyme-linked immunosorbent assay. Results: Of the 168 individuals with CTD, 70 had primary Sjögren's syndrome (pSS), 64 had systemic sclerosis (SSc), and 34 had polymyositis/dermatomyositis (PM/DM). There were 116 cases with concurrent ILD; ILD scores were 1 (n=23), 2 (n=41), and 3 (n=52). Serum MUC5AC and MUC5B protein levels were considerably higher in CTD-ILD than CTD-only individuals or healthy controls (both p<0.005). Among the CTD subgroups, MUC5AC was higher in individuals with concurrent ILD than in those without ILD (all p<0.05). MUC5AC was positively correlated with ILD severity in all three CTD subgroups (all R>0.47 and all p<0.05). The MUC5B levels varied substantially between SSc and SSc patients with concurrent ILD (p=0.032) and were related to ILD severity only in PM/DM patients (R=0.346 and p=0.045). Conclusion: MUC5AC is correlated with the occurrence and development of ILD, while MUC5B is associated with ILD diagnosis and severity in CTD subgroups. Serum MUC5AC levels present a definite diagnostic utility for CTD-ILD and as proxies for its severity.